A study of leukemias Profile in central India - Dr. Rajnikant Ahirwar; Dr. Rajendra Kumar Nigam; Dr. Deepankar Parmar (Tropical Journal of Pathology and Microbiology, 2018)
Introduction: Leukemia was considered as a rare disease few years back. However, it is increasing in incidence and prevalence slowly and steadily. Leukemias are euplastic proliferations of haematopoietic cells and form a major proportion of haematopoietic neoplasms that are diagnosed worldwide. Objective: To find out the incidence of four major types of leukemias in central India. Methods: Total 73 cases were selected from in and out patient departments of Gandhi Medical College and associated Hamidia Hospital Bhopal over a period from Oct 2013 to Nov 2014. Diagnosis was based on peripheral blood count, peripheral blood smear and bone marrow examination for morphology along with cytochemistry study whenever required. Results: Out of 73 cases on final diagnosis, 23 cases (31.51%) were of Acute Lymphoblastic Leukemias, 11 cases (15.07%) were of Acute Myeloblastic Leukemias, 35 cases (47.97%) were of Chronic Myeloid Leukemias, 1 case (1.37%) is of Chronic Lymphocytic Leukemia and 3 cases (4.11%) were Undiagnosed which were referred to higher centers. Conclusion: The present study revealed that Chronic leukemia was more common than acute leukemia with Chronic Myeloid Leukemias being the most common type, followed by Acute Lymphoblastic Leukemias, Acute Myeloblastic Leukemias and Chronic Lymphocytic Leukemia.